ICTs and development in India : perspectives on the rural network society - Sreekumar, T. T. (London : Anthem Press, 2011)
'ICTs and Development in India' is a unique attempt to study the nature and consequences of the growing presence of Information Technology in development projects in India.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Information technology -- India; Communication in rural development -- India; Rural development projects -- India